2020
DOI: 10.1093/cid/ciaa310
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Early Humoral Response to Diagnose Novel Coronavirus Disease (COVID-19)

Abstract: Background The emergence of coronavirus disease 2019 (COVID-19) is a major healthcare threat. The current method of detection involves a quantitative polymerase chain reaction (qPCR)–based technique, which identifies the viral nucleic acids when present in sufficient quantity. False-negative results can be achieved and failure to quarantine the infected patient would be a major setback in containing the viral transmission. We aim to describe the time kinetics of various antibodies produced ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

100
1,725
11
112

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,574 publications
(1,948 citation statements)
references
References 16 publications
100
1,725
11
112
Order By: Relevance
“…Serologic tests that identify antibodies (such as IgA, IgM, and IgG) to SARS-CoV-2 from clinical specimens (such as blood or saliva), such as enzyme-linked immunosorbent assays, may be less complex than molecular tests and have the potential to be used for diagnosis in certain situations (46). However, their utility for diagnosing acute infections is probably limited around the time of symptom onset, when viral shedding and transmission risk seem to be highest (32).…”
Section: Serologymentioning
confidence: 99%
See 1 more Smart Citation
“…Serologic tests that identify antibodies (such as IgA, IgM, and IgG) to SARS-CoV-2 from clinical specimens (such as blood or saliva), such as enzyme-linked immunosorbent assays, may be less complex than molecular tests and have the potential to be used for diagnosis in certain situations (46). However, their utility for diagnosing acute infections is probably limited around the time of symptom onset, when viral shedding and transmission risk seem to be highest (32).…”
Section: Serologymentioning
confidence: 99%
“…However, their utility for diagnosing acute infections is probably limited around the time of symptom onset, when viral shedding and transmission risk seem to be highest (32). Antibody responses to infection take days to weeks to be reliably (46). Negative results would not exclude SARS-CoV-2 infection, particularly among those with recent exposure to the virus.…”
Section: Serologymentioning
confidence: 99%
“…Nucleocapsid protein is a 50 KDa protein commonly involved in the replication, transcription and packaging of the viral genome, other than hindering the reproductive cycle of the host cell [11]. Also, NC is the most abundant protein in coronaviruses, is highly immunogenic and its amino acid sequence is normally conserved, making of this protein a suitable candidate target for both vaccine formulations and diagnostic assays [12,13]. Previous studies on SARS-CoV reported NC protein epitopes as capable of eliciting a massive production of antibodies in infected subjects while its prevalence was significantly reduced in convalescent patients, suggesting such epitopes as candidates for the design of diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to address this challenge have already been suggested, that can be categorized into three major approaches. The first approach is to replace PCR based methods by other direct diagnostic methods such as Loopmediated Isothermal Amplification (LAMP) [1][2][3] and CRISPR based diagnostic tools [4][5][6], the second approach involves serological surveys [7][8][9][10], and the third approach involves the improvement of the PCR methods capacity by optimization and automation (e.g. [11][12][13]) or by reducing the required number of tests via pooling samples together, known as group testing.…”
Section: Introductionmentioning
confidence: 99%